Coeliac screening in a Scottish cohort of children with type 1 diabetes mellitus: is DQ typing the way forward?. Issue 3 (30th December 2015) - Mitchell, R T; Sun, A; Mayo, A; Forgan, M; Comrie, A; Gillett, P M
Abstract : Background: Children with type 1 diabetes mellitus (T1DM) are at increased risk of coeliac disease (CD). Recent guidelines indicate coeliac screening should include HLA typing for CD predisposing (DQ2/DQ8) alleles and those negative for these alleles require no further coeliac screening. Methods: Children (n=176) with T1DM attending clinics across two Scottish regions were screened for HLA DQ2/DQ8 as part of routine screening. Data collected included the frequency of DQ2/DQ8 genotypes and the additional cost of HLA screening. Results: Overall, DQ2/DQ8 alleles were identified in 94% of patients. The additional cost of HLA typing was £3699.52 (£21.02 per patient). All patients with known CD (11/176) were positive for DQ2/DQ8 and all were diagnosed with CD within 5 years of T1DM diagnosis. Conclusions: The vast majority of children with T1DM have CD-predisposing HLA genotypes limiting the number of patients that can be excluded from further screening. We conclude that HLA genotyping is not currently indicated for CD screening in this population.